2002
DOI: 10.1002/ddr.10102
|View full text |Cite
|
Sign up to set email alerts
|

Design, syntheses, and evaluation of 2,3‐diphenylcycloprop‐2‐en‐1‐ones and oxime derivatives as potential cyclooxygenase‐2 (COX‐2) inhibitors with analgesic‐antiinflammatory activity

Abstract: A group of 2,3-diphenylcycloprop-2-enes having a variety of substituents at the paraposition of the C-2 phenyl ring (H, F), and C-3 phenyl ring (H, F, SMe, SOMe, SO 2 Me), in conjunction with either a C-1 carbonyl, oxime, oxime acetate, benzoyl hydrazone, or hydrogen substituent were synthesized for in vivo evaluation as analgesic and antiinflammatory (AI) agents, and as potential selective cyclooxygenase-2 (COX-2) inhibitors. This group of cycloprop-2-ene compounds exhibited significant analgesic activity, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Cyclopropenes 1a , 1b , 1c , 1o , 1d , 1e , 1f , 1l , 1m , 1g – j , 1k , 1n , 2a , 2b , 2c , 2d , 2e , 2f , 2g – i , 3b , and 3c were prepared according to the literature data. Parent cyclopropene ( 3a ) was obtained according to a literature procedure with slight modifications .…”
Section: Methodsmentioning
confidence: 99%
“…Cyclopropenes 1a , 1b , 1c , 1o , 1d , 1e , 1f , 1l , 1m , 1g – j , 1k , 1n , 2a , 2b , 2c , 2d , 2e , 2f , 2g – i , 3b , and 3c were prepared according to the literature data. Parent cyclopropene ( 3a ) was obtained according to a literature procedure with slight modifications .…”
Section: Methodsmentioning
confidence: 99%
“…All reagents were used as purchased from commercial suppliers without further purification. Starting materials that were not commercially available were synthesized by the previously reported methods. , All solvents were dried by standard procedures and freshly distilled prior to use. The progress of reactions was monitored by TLC on Silufol UV-254 plates using UV light and iodine for detection.…”
Section: Methodsmentioning
confidence: 99%
“…Based upon this hypothesis, compounds with vicinal diaryl rings on cycloprop-2-en-1-one have been investigated as COX-2 inhibitors. In-vitro COX-1 and COX-2 inhibition studies showed that 2,3-diphenylcycloprop-2-en-1-one oxime 105 (Chart 35) is a selective COX-2 inhibitor [95]. Among a group of (Z)-and (E)-1,1-dihalo-2-(4-substituted-phenyl)-3-phenylcyclopropanes evaluated for analgesic and anti-inflammatory properties, compound 106 (Chart 35) with E-configuration inhibited COX-1 (IC 50 = 278.8 M) and COX-2 (IC 50 = 80.5 M) for a COX-2 selectivity index of 3.5 [96].…”
Section: -Membered Carbocycles As the Central Core Of Cox-2 Inhibitorsmentioning
confidence: 99%